Analysis of the Effectiveness and Contribution of Hotel Tax, Restaurant Tax and Local Tax to Local Revenue in the Special Region of Yogyakarta - Sulaiman Ahmad; Rosyid Nur Anggara Putra (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Purpose: This study aimed to determine the effect of the effectiveness of hotel taxes, restaurant taxes, and regional taxes on Local Revenue and the magnitude of the tax contribution to district/city Local Revenue in the Special Region of Yogyakarta. Methodology : This research was conducted on all hotel tax and restaurant tax data in five regencies/cities in the Special Region of Yogyakarta, which includes all types of hotels and restaurants as stipulated in Law Number 28 of 2009 concerning Regional Taxes and Regional Levies for the 2011-2019 period. This research includes descriptive research that uses a quantitative approach. Findings: The results showed that the hotel tax's and restaurant tax's effectiveness had no significant effect. The effectiveness of the local tax significantly negatively affected the Local Revenue of districts/cities in the Special Region of Yogyakarta from 2011 to 2019. The highest effectiveness of hotel taxes occurred in 2021 in Bantul Regency at 658.70%, and the lowest in 2015 was in Bantul Regency at 12.68%. In the restaurant tax, the highest level of effectiveness occurred in 2012 in Bantul Regency at 225.99% and the lowest in 2015 in Sleman Regency at 88.12%. Overall tax contributions from 2011 to 2019 contributed equally to Local Revenue Novelty: This study continues previous research by using a different population specially in district/city Yogyakarta Special Region.